Literary masters trapped in a woman’s body: The Latin American Boom under the epithet of ¨¨"club de machos" - Arevalo, Emily (Ánima, 2023)
The Latin American boom came to be, due to the sociocultural and literary context in which it developed: the 1960s and 1970s. Therefore, the literary conception held by the movement can be attributed to the strong social influences of the time. One of the features of note when revising a list of boom authors is the lack of female names. While a literary explosion on such a scale cannot be expected to be thoroughly planned with equality in mind, this does not mean that the epithet "macho club" is inappropriate when characterizing the movement. With the goal of determining whether the above epithet can encompass the Latin American boom, the case of three authors will be studied: Albalucía Ángel, Clarice Lispector and Elena Garro.